Seizures and Consciousness Disorder Secondary to Intracranial Hypotension After Spinal Surgery: A Case Report and Literature Review - Lv, Yuqing; Xiang, Hui (Frontiers in Neurology, 2022)
Rationale Cerebrospinal fluid (CSF) leakage is a common condition after spinal surgery and is also the most common cause of intracranial hypotension. Intracranial hypotension (IH) is typically characterized by an orthostatic headache with associated nausea, vomiting, tinnitus, vertigo, hypoacusis, neck stiffness, and photophobia. There have been limited case reports describing surgery-associated IH presenting with seizures and disorder of consciousness. Due to the atypia of symptoms, these clinical manifestations are usually ignored or even misdiagnosed. As a result, clinicians face a significant challenge in detecting IH early and understanding its various clinical presentations. Meanwhile, we summarize the cases of IH presenting as seizures in recent years, including its clinical characteristics and effective treatment, which will be very helpful for the early diagnosis of IH. Patient concerns A 72-year-old Chinese male patient developed status epilepticus, a disorder of consciousness, and quadriplegia when he finished spinal surgery, although he had no previous seizures or any seizure risk factors. Diagnosis After MRI and CT examination, subdural hygromas were found under both sides of the skull, and combined with the clinical manifestations of the patient, intracranial hypotension due to cerebrospinal fluid leakage was diagnosed. Interventions In the early stage, we carried out strict perioperative critical care for the patient. Trendelenburg position was conducted to relieve intracranial hypotension. The dural repair surgery was performed after the diagnosis of CSF leakage. Outcomes Seizures in the patient were resolved. Three months after discharge, he was gradually returning to normal life. Lessons One possible cause of unexplained seizures and disorder of consciousness after spinal surgery is cerebrospinal fluid leakage associated with intracranial hypotension syndrome. Trendelenburg position and dural repair surgery are effective ways to relieve intracranial hypotension and associated symptoms. Better awareness of the association between IH (intracranial hypotension) and seizures may help us improve early recognition of the syndrome.